Identification of the methionine transporter MetQ in Streptococcus suis and its contribution to virulence and biofilm formation - Camila Bosch; Carla García; Luis Saralegui; Lucille van Beek; Marien I. de Jonge; Clara Marín; Jesús Arenas (Veterinary Research)
Abstract Streptococcus suis is a Gram-positive bacterium responsible for various infections in both pigs and humans. This study investigates the role of methionine acquisition in the growth and virulence of S. suis. The putative methionine transport system is organised as an operon comprising the metQ gene and genes encoding a transposase and an ATPase, forming a typical tripartite ABC transporter. This operon is conserved across multiple streptococcal species, including both animal and human pathogens. We examined whether MetQ functions as a methionine-binding protein and its role in bacterial infection. Using Western blotting and flow cytometry with a specific antiserum, we demonstrated that MetQ is produced in vitro by the S. suis reference strain P1/7 under methionine-limited conditions and is located on the bacterial cell surface. Growth assays in chemically defined media revealed that a metQ deletion mutant (P1/7∆metQ) exhibited impaired growth under methionine-restricted conditions but grew normally in a nutrient-rich medium, suggesting that MetQ primarily transports methionine. Isothermal Titration Calorimetry demonstrated that MetQ binds L-methionine with a dissociation constant (KD) of 7.1 µM. In a murine infection model, the metQ mutant showed reduced dissemination to internal organs compared to the wild type. Furthermore, the mutant showed decreased intracellular survival in murine macrophages and increased sensitivity to oxidative stress, while exhibited enhanced biofilm formation compared to the wild type. Our findings indicate that MetQ is essential for methionine uptake under methionine-restricted conditions, which is critical for bacterial nutrition, immune evasion, and pathogenicity during infection.